2011
DOI: 10.1111/j.1574-6968.2011.02342.x
|View full text |Cite
|
Sign up to set email alerts
|

Typing of bacteriophages by randomly amplified polymorphic DNA (RAPD)-PCR to assess genetic diversity

Abstract: The recent boom in phage therapy and phage biocontrol requires the design of suitable cocktails of genetically different bacteriophages. The current methods for typing phages need significant quantities of purified DNA, may require a priori genetic information and are cost and time consuming. We have evaluated the randomly amplified polymorphic DNA (RAPD)-PCR technique to produce unique and reproducible band patterns from 26 different bacteriophages infecting Staphylococcus epidermidis, Staphylococcus aureus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…Diana Gutiérrez et al (2011) have suggested that cocktails composed of phages with different genetic characteristics are more effective in phage therapy. They have shown that band patterns obtained by RAPD-PCR are an easy and reproducible method for bacteriophage typing (30).…”
Section: Discussionmentioning
confidence: 99%
“…Diana Gutiérrez et al (2011) have suggested that cocktails composed of phages with different genetic characteristics are more effective in phage therapy. They have shown that band patterns obtained by RAPD-PCR are an easy and reproducible method for bacteriophage typing (30).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from colonies as described above. Primers OPL5 (5'-ACGCAGGCAC-3'), RAPD5 (5'-AACGCGCAAC-3'), P1 (5'-CCGCAGCCAA-3') were used according to Gutiérrez et al (2011). RAPD-PCR reactions were performed with the following cycling program: four cycles at 94 °C for 45 s, 30 °C for 120 s and 72 °C for 60 s; 26 cycles at 94 °C for 5 s, 36 °C for 30 s and 72 °C for 30 s and a final step of 10 min at 75 °C.…”
Section: Genetic Fingerprinting By Rapd-pcrmentioning
confidence: 99%
“…Phages were induced by UV light and purified as described in Materials and Methods. At the end of the treatment with UV, the phage count was estimated by epifluorescence at 10 10 phage/ml, 1 log unit higher than that reported to be needed for optimal reproducibility (29). The 15 phage DNAs were subjected to two RAPD-PCRs, one using only the random primer M13 and, to increase the sensitivity of the profiles (22), a second one with primers M13 and Lys20_fw.…”
Section: Pcr Screening and Phage Characterization By Lys Prophage Seqmentioning
confidence: 99%